PENGGUNAAN E-BOOK UNTUK MENINGKATKAN MINAT BACA SISWA SEKOLAH MENENGAH PERTAMA - Puji Fitriyanti (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study was to analyze the increase in reading interest through the use of e-books in class IX D SMPN 2 Mayang.The method used in this research is Guidance and Counseling Action Research (PTBK) which was carried out in two cycles. Each cycle includes four stages of planning, implementing action, observing and reflecting. The subjects in this study were students of class IX D in the 2020/2021 academic year as many as 30 students. Data collection techniques using test, observation and interview techniques. Data were analyzed qualitatively and quantitatively.Based on the observation of the initial conditions before the study was conducted, the percentage of students' interest in reading was only 37%. After the action was taken, namely the use of e-books as a source of literacy in guidance and counseling services, the percentage of students' interest in reading increased. In cycle 1 the percentage of students' completeness increased to 50% while in cycle 2 it reached 70%. This increase in the percentage of students' reading interest shows that the use of e-books as a reading source in digital literacy has succeeded in increasing students' reading interest.